Functionalization of cellulose nanocrystals with N-vinylcaprolactam, spermine dendrons, and glucuronic acid for tumor targeting and controlled release of gemcitabine - Fakhraldin Masoumi Jadval Ghadam; Mehdi Faramarzi; Homayon Ahmad Panahi; Seyed Aboutaleb Mousavi Parsa (Results in Chemistry)
One of the main challenges in prostate cancer treatment is achieving precise drug delivery and controlled release of chemotherapeutic agents to enhance their efficacy, while reducing systemic toxicity. In this study, an advanced nanodrug delivery system (NDDS) was designed for targeted gemcitabine delivery based on a graft copolymer. The copolymer CNC-g-(NVCL-co-ALA) was synthesized via redox-initiated polymerization of N-vinyl caprolactam (NVCL) and allylamine (ALA) onto cellulose nanocrystals (CNC) using cerium ions as the initiator. To enhance tumor targeting, first-generation spermine dendrons conjugated with glucuronic acid were incorporated to enable dual-ligand active targeting. Comprehensive characterization using 1H NMR, FT-IR, TGA, TEM, FESEM, AFM, BET, DLS, zeta potential analysis, and UV–Vis transmittance confirmed the structural and physicochemical properties of the system. NDDS demonstrated a high and rapid gemcitabine loading capacity (477 mg/g) through exothermic and physical adsorption. Drug release studies demonstrated pH- and temperature-dependent behavior, with 92.4 % release at pH 4.5 and 40 °C, while less than 10 % release occurred under physiological conditions (pH 7.4, 37 °C), effectively minimizing premature drug leakage. Kinetic modeling confirmed a Fickian diffusion-controlled release mechanism, following the Weibull model, with a predicted half-life of 12.35 h. Biocompatibility was validated through MTT assays, and cytotoxicity studies showed that NDDS-loaded gemcitabine significantly reduced prostate cancer cell viability compared to free gemcitabine. These findings highlight NDDS as a promising nanocarrier for prostate cancer therapy, providing targeted drug delivery, controlled drug release, and enhanced therapeutic efficacy.